2019
DOI: 10.1038/s41598-019-56265-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental arthritis and Porphyromonas gingivalis administration synergistically decrease bone regeneration in femoral cortical defects

Abstract: Porphyromonas gingivalis infection can lead to periodontitis and dysbiosis, which are known risk factors for rheumatoid arthritis (RA). We investigated whether P. gingivalis administration affected bone regeneration in mice with or without arthritis. We administered P. gingivalis to male DBA/1 J mice that were or were not sensitised to type II collagen-induced arthritis (CIA). All mice underwent drilling of bilateral femurs. We histologically evaluated new bone regeneration (bone volume of the defect [BVd]/tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Bone exposure, lack of socket healing and osteonecrosis were present in jaws of most ZA-treated animals after extraction of teeth and bacterial presence was noted in areas of osteonecrotic alveolar bone ( de Molon et al., 2014 ; Kuroshima et al., 2018b ; Hadaya et al., 2019 ). In our study, we artificially put the femur in an environment that had direct contact with P. gingivalis and observed the healing of defects ( Okumura et al., 2019 ). We found after administration of ZA, the femurs locally injected with P. gingivalis as well as the mandibles showed poor healing of wounds, with reduced bone volume and collagen fiber regeneration, increased empty lacunae and inflammatory infiltration, and declined active osteoclasts in the affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Bone exposure, lack of socket healing and osteonecrosis were present in jaws of most ZA-treated animals after extraction of teeth and bacterial presence was noted in areas of osteonecrotic alveolar bone ( de Molon et al., 2014 ; Kuroshima et al., 2018b ; Hadaya et al., 2019 ). In our study, we artificially put the femur in an environment that had direct contact with P. gingivalis and observed the healing of defects ( Okumura et al., 2019 ). We found after administration of ZA, the femurs locally injected with P. gingivalis as well as the mandibles showed poor healing of wounds, with reduced bone volume and collagen fiber regeneration, increased empty lacunae and inflammatory infiltration, and declined active osteoclasts in the affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the severity of arthritis in Pg ‐inoculated experimental mice and found that Pg infection triggers changes in the commensal oral microbiota and induces inflammation‐mediated periodontal bone loss and also exacerbates arthritis 37 . In general, collagen‐induced arthritis (CIA) murine models experience high systemic inflammation 21 and lower callus volumes. Accumulating evidence suggests an increase in incidence and severity of RA based on data showing increased expression of inflammatory mediators like pro‐inflammatory cytokines.…”
Section: The Oral Microbiota and Arthritismentioning
confidence: 99%
“…20 The oral cavity includes over 700 bacterial species and serves as the second-largest microbial niche after the gastrointestinal tract. 8,21,22 For this reason, the host is at further risk for additional health-related problems due to the relatively high prevalence of pathogenic bacteria that can infect the mouth and neighboring structures and organs. 23 When the microbial community is imbalanced, immunoregulatory properties are seemingly disrupted.…”
Section: The or Al MI Crob I Ota And Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…The cytokine signature of each disease is similar with an increased expression of proinflammatory cytokines, TNF-α and IL-6. In murine models of experimental arthritis, it was found that there is an increase in the serum levels of these inflammatory mediators following oral administration of periodontal pathogens, supporting their role in exacerbating the local and systemic inflammation associated with RA [ 67 , 68 , 69 ]. Additionally, auto-antibodies such as rheumatoid factor and anticollagen antibodies common to RA are often found in diseased periodontal tissues [ 70 , 71 ].…”
Section: P Gingivalis and Rheumatoid Arthritismentioning
confidence: 99%